1975
DOI: 10.4141/cjps75-072
|View full text |Cite
|
Sign up to set email alerts
|

THE BIOLOGY OF CANADIAN WEEDS.: 11. Ambrosia artemisiifolia L. and A. psilostachya DC.

Abstract: This account of Ambrosia artemisiifolia L. (common ragweed)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
275
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(285 citation statements)
references
References 2 publications
3
275
1
6
Order By: Relevance
“…Observations done in another area in southern Quebec where ragweed is widespread, also suggested that ragweed was more abundant along roadsides than in other rural settings (Comtois 1995 surveyed field entrances in the Saint-Jean-sur-Richelieu area located away from major axes of transport. Along these often private farm roads lower disturbance, light intensity and use of de-icing salt potentially lead to lower ragweed abundance (Basset and Crompton 1975;DiTommaso 2004). Weeds that are more associated with fields than roadsides, but can be found along roadsides, specifically Amaranthus species (Costea et al 2004), were not observed along rural roadsides, even in the area closest to the field entrances.…”
Section: Discussion Fields Field Borders and Roadsidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Observations done in another area in southern Quebec where ragweed is widespread, also suggested that ragweed was more abundant along roadsides than in other rural settings (Comtois 1995 surveyed field entrances in the Saint-Jean-sur-Richelieu area located away from major axes of transport. Along these often private farm roads lower disturbance, light intensity and use of de-icing salt potentially lead to lower ragweed abundance (Basset and Crompton 1975;DiTommaso 2004). Weeds that are more associated with fields than roadsides, but can be found along roadsides, specifically Amaranthus species (Costea et al 2004), were not observed along rural roadsides, even in the area closest to the field entrances.…”
Section: Discussion Fields Field Borders and Roadsidesmentioning
confidence: 97%
“…Field borders were generally composed of graminoid species [probably mostly perennial grasses like Bromus inermis (deBlois et al 2002)], perennial and biennial species. An increase in perennial cover and a reduction in disturbance reduce ragweed abundance (Gebben 1965;Basset and Crompton 1975;Maryushkina 1991;DiTommaso and Massicotte 2002). This explains the low ragweed abundance in field borders relative to fields where herbicides are applied.…”
Section: Discussion Fields Field Borders and Roadsidesmentioning
confidence: 99%
“…On undisturbed soil, the annual seed production of ragweed germinates to high percentages in early next spring (Dickerson 1968, Bassett and Crompton 1975, Fumanal et al 2008, Kazinczi et al 2008. Soil tillage incorporates new seeds into deeper layers of the soil (Buhler et al 1997) and promotes long time persistency of ragweed seeds (Toole and Brown 1946).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby the normal succession of vegetation can be impeded or disturbed by the invasion of S. ciliatum, as has been shown for other adventive plants in long term experiments with permanent plots [74,75]. After cessation of the disturbing factors the abundance and dominance of S. ciliatum will decrease markedly, as for other herbaceous invasive therophytes [74,76,77] and, on wet and salty fields, by increasing the share of perennial species the analysed phytocoenoses may evolve into more stable halophilous communities, such as Astero tripoli-Juncetum gerardii, widespread in the study area [7] or in other similar communities from the class Festuco-Puccinellietea.…”
Section: Syndynamic Aspectsmentioning
confidence: 99%